Time issues in strategy and organization - Das, T. K. 1938- (Research in strategy science., 2019)
"The field of strategy science has grown in both the diversity of issues it addresses and the increasingly interdisciplinary approaches it adopts in understanding the nature and significance of problems that are continuously emerging in the world of human endeavor. These newer kinds of challenges and opportunities arise in all forms of organizations, encompassing private and public enterprises, and with strategies that experiment with breaking the traditional molds and contours. The field of strategy science is also, perhaps inevitably, being impacted by the proliferation of hybrid organizations such as strategic alliances, the upsurge of approaches that go beyond the customary emphasis on competitiveness and profit making, and the intermixing of time-honored categories of activities such as business, industry, commerce, trade, government, the professions, and so on. The blurring of the boundaries between various areas and types of human activities points to a need for academic research to address the consequential developments in strategic issues. Hence, research and thinking about the nature of issues to be tackled by strategy science should also cultivate requisite variety in issues recognized for research inquiry, including the conceptual foundations of strategy and strategy making, and the examination of the critical roles of strategy makers, strategic thinking, time and temporalities, business and other goal choices, diversity in organizing modes for strategy implementation, and the complexities of managing strategy, to name a few. This book series on Research in Strategy Science aims to provide an outlet for ideas and issues that publications in the field do not provide, either expressly or adequately, especially as regards the comprehensive coverage deserved by certain emerging areas of interest. The topics of the volumes in the series will keep in view this objective to expand the research areas and theoretical approaches routinely found in strategy science, the better to permit expanded and expansive treatments of promising issues that may not sufficiently align with the usual research coverage of publications in the field. Time Issues in Strategy and Organization contains contributions by leading scholars on time issues in the field of strategy science research. The 8 chapters in this volume cover topics such as future orientation in strategy making, time conceptualizations in interorganizational relationships, real-time management in the digital economy, spatio-temporal aspect of strategic leadership, a systemic-cognitive perspective on organizational temporality, ecosystem types and the timing of open innovation strategies, and the temporalities of strategic risk behavior and partner opportunism in strategic alliances. The chapters collectively present a wide-ranging review of the noteworthy research perspectives on the temporal issues in strategy and organization"--